2005
DOI: 10.1093/ejo/cji050
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of three orthodontic brackets: a comparative study of three fluoride mouthwashes

Abstract: In the present study, three types of orthodontic brackets were investigated: cobalt-chromium (CoCr), iron-chromium-nickel (FeCrNi) and titanium (Ti) based. Their corrosion resistance was compared with that of platinum (Pt), which was chosen as the reference material because of its excellent electrochemical properties. The test solutions were Elmex, Meridol and Acorea fluoride mouthwashes. Fusayama Meyer artificial saliva was used as the reference solution. The corrosion resistance of the different brackets in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
53
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 23 publications
5
53
0
7
Order By: Relevance
“…In an acidic environment, corrosion could easily occur even with low fluoride concentrations; 32 pitting type of corrosion is caused by anions, such as chloride and fluoride ions which attack the protective oxide layer. 33 Manganese and copper were the highest in ALO mouthwash, although these results disagreed with Singh 34 who found that ALO has inhibition efficiency of corrosion lying between 22 and 73% at different concentrations; however, there are several possible explanations for these results. It seems possible due to Cu ion percentage in the stainless steel alloy of bracket and the chemical composition of mouthwash.…”
Section: Discussionmentioning
confidence: 66%
“…In an acidic environment, corrosion could easily occur even with low fluoride concentrations; 32 pitting type of corrosion is caused by anions, such as chloride and fluoride ions which attack the protective oxide layer. 33 Manganese and copper were the highest in ALO mouthwash, although these results disagreed with Singh 34 who found that ALO has inhibition efficiency of corrosion lying between 22 and 73% at different concentrations; however, there are several possible explanations for these results. It seems possible due to Cu ion percentage in the stainless steel alloy of bracket and the chemical composition of mouthwash.…”
Section: Discussionmentioning
confidence: 66%
“…This is considered a consequence of the release of the trace amounts of silver and copper present in some commonly used solutions, tubes, bottles, bottle caps, and clips. Although there are several studies that have investigated corrosion on orthodontic appliances caused by mouthwashes, 19,[28][29][30] there are not many studies that have investigated the effects of mouthwashes on different soldering applications. Our finding is that the greatest amount of metal ion release occurs in NaF + alcohol containing mouthwashes and may contribute to both the literature and to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 It has been reported that mouthwashes increase the risk of corrosion and cause the release of some metals from the surface of orthodontic appliances. [27][28][29][30] There are no prior studies in the literature that investigate the relationships between various mouthwashes, metal ion release, and various soldering methods. The aim of the present study was to compare the release of nickel, chromium, iron, silver, and copper ions; the corrosion rate; and the amount of corrosion for two different soldering methods used in the preparation of orthodontic appliances-laser welding and silver soldering-in three different mouthwash solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different techniques are currently being used to obtain coatings of biotolerable materials with mechanical strength and with a bioactive layer [11,12]. Coatings can be produced, for example, by ion sputtering, plasma spraying, sol-gel, electrolysis, and biomimetic methods [6].…”
Section: Introductionmentioning
confidence: 99%